The Girls of St. Wode's - Meade, L. T., 1854-1914 (Salt Lake City, UT : Project Gutenberg, 2012)
"The Girls of St. Wode's" by L. T. Meade is a novel written in the late 19th century. The story centers around three young women$1 (Btwins Eileen and Marjorie Chetwynd, and their cousin Letitia$1 (Bas they navigate the transition from school to society. The narrative explores themes of modernity, individual choice, and the expectations placed upon young women regarding their roles in society. At the start of the book, Eileen, Marjorie, and Letitia are coming home from school, signaling a pivotal moment in their lives as they prepare for their debut in fashionable society. Conversations between their mother, Mrs. Chetwynd, and her friend Mrs. Acheson highlight differing views on education and societal roles for women. Meanwhile, Eileen and Marjorie express their reluctance to conform to conventional societal expectations, eagerly discussing their plans to lead independent lives and consider attending St. Wode's College for further education. This sets the stage for their ongoing conflict with their mother, who has specific ambitions for their debut in high society. (This is an automatically generated summary.)s
Release date is 2012-11-09
E-text prepared by Roger Frank and the Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Christian life -- Juvenile fiction; Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; Siblings -- Juvenile fiction; Kindness -- Juvenile fiction; Students -- Juvenile fiction; Poverty -- Juvenile fiction; Youth -- Conduct of life -- Juvenile fiction; Theft -- Juvenile fiction; Temptation -- Juvenile fiction; Forgery -- Juvenile fiction; Debt -- Juvenile fiction